Body Posture Position Alarm Prototype Based on NodeMCU ESP8266 - Setyawan, Candra Dwi; Wisaksono, Arief (Universitas Ahmad Dahlan, 2023)
Lack of physical activity has a negative impact, namely reduced motor coordination abilities and changes in posture or shape of the spine. Sitting positions that are more static and less ergonomic, such as sitting in a hunched position, can trigger significant muscle activation. Therefore, in an effort to prevent bone abnormalities, research was carried out regarding a prototype body posture alarm based on the NodeMCU ESP8266. This prototype uses a flexible sensor to read spinal curvature integrated into the NodeMCU ESP8266 and a buzzer as the output. This prototype will be attached to the back support shoulder, so this prototype design can also help repair bones that have been damaged due to bad sitting habits. In general, this prototype reminds users to always be in a normal body position by making a sound when the body position is not normal. From the test results, the prototype works well. NodeMCu's speed in capturing WiFi signals is fast enough so that the prototype works quickly, flexible sensor readings are accurate without using an amplifier. The back support shoulder design is very efficient in helping users to maintain a normal body position.